2008
DOI: 10.1128/aac.00194-08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Minocycline and Valproic Acid Coadministration on Atazanavir Plasma Concentrations in Human Immunodeficiency Virus-Infected Adults Receiving Atazanavir-Ritonavir

Abstract: Minocycline and valproic acid are potential adjuvant therapies for the treatment of human immunodeficiency virus (HIV)-associated cognitive impairment. The purpose of this study was to determine whether minocycline alone or in combination with valproic acid affected atazanavir plasma concentrations. Twelve adult HIV-infected subjects whose regimen included atazanavir (300 mg)-ritonavir (100 mg) daily for at least 4 weeks were enrolled. Each subject received atazanavir-ritonavir on day 1, atazanavir-ritonavir p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In concentration time profiles of existing plasma samples, the C max and AUC of RTV [34, 35] were similar as previously reported [29]. Metabolite profiles showed formation rate limited clearance except for R5 indicating a lower clearance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In concentration time profiles of existing plasma samples, the C max and AUC of RTV [34, 35] were similar as previously reported [29]. Metabolite profiles showed formation rate limited clearance except for R5 indicating a lower clearance.…”
Section: Discussionsupporting
confidence: 84%
“…): measured by depletion 1 [6, 34] 2 inhibition measured with specific probes in Supersomes [27] [11] 3 R<0.2 4 Linear scaled according to k inact /K I, see materials and methods, n.d.: not determined) 5 95% confidence interval. …”
Section: Figurementioning
confidence: 99%
“…A class III study in 11 HIV‐positive subjects (eight evaluable) taking lopinavir/ritonavir 400/100 found that lopinavir AUC increased on average by 38% (90% CI −2% to 94%) after administration of valproic acid 500 mg/day for 7 days (DiCenzo et al., 2004). A class III study of HIV‐positive subjects showed no effect of valproic acid on atazanavir (12 subjects) or ritonavir (9 subjects) levels (DiCenzo et al., 2008).…”
Section: Analysis Of the Evidencementioning
confidence: 99%
“…177 Another prospective study containing ritonavir and atazanavir found no significant results when co-administered with valproic acid. 178 However, 2 studies did find DDIs with valproic acid when the PI combination product lopinavir/ritonavir was co-administered. In the case report, the patient experienced decreased valproic acid concentrations, likely due to ritonavir-induced metabolism, which resulted in clinical symptoms of mania/hypomania.…”
Section: Carbamazepinementioning
confidence: 99%